Perancangan Media pembelajaran Interaktif Pengenalan Sistem Tata Surya Untuk Siswa Sekolah Dasar - Shafa Yasinta Agustina; Riyan Abdul Aziz (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Technology is currently developing at a very fast pace. The teaching and learning process in the field of education is greatly impacted by the ever-improving technology advancements. In order to spark students' interest in studying, a lot of schools and teachers are currently utilizing technology tools like interactive learning media. In order to increase students' enthusiasm in learning, teachers' inventiveness is equally crucial. Learning media is a crucial component that may draw students in and aid in their pursuit of the best possible learning outcomes. Engaging media helps pupils comprehend the lessons that are being taught. Therefore, the goal of creating interactive learning materials to present the solar system to pupils is to enable them to view the actual things rather than only envision them.